2021
DOI: 10.1101/2021.02.24.432639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliance of neuronal gene expression on cohesin scales with chromatin loop length

Abstract: Cohesin and CTCF are major drivers of 3D genome organization. Even though human mutations underscore the importance of cohesin and CTCF for neurodevelopment, their role in neurons is only just beginning to be addressed. Here we conditionally ablate Rad21 in cortical neurons, revealing a prominent role for cohesin in the expression of genes that facilitate neuronal maturation, homeostasis, and activation. In agreement with recent reports, activity-dependent genes were downregulated at baseline. However, in cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 98 publications
(275 reference statements)
1
8
0
Order By: Relevance
“…It is therefore perhaps not surprising that only a subset of genes is mis-regulated upon cohesin depletion, since loss of cohesin might only effect genes whose expression is critically dependent on the robust formation of tissue-specific enhancer-promoter interactions. This is consistent with the reported importance of cohesin for regulating gene expression upon stimuli and during differentiation 43,44 .…”
Section: Mainsupporting
confidence: 92%
“…It is therefore perhaps not surprising that only a subset of genes is mis-regulated upon cohesin depletion, since loss of cohesin might only effect genes whose expression is critically dependent on the robust formation of tissue-specific enhancer-promoter interactions. This is consistent with the reported importance of cohesin for regulating gene expression upon stimuli and during differentiation 43,44 .…”
Section: Mainsupporting
confidence: 92%
“…Therefore, promoters positioned proximally to differential TAD boundaries in neurons may interact efficiently with their enhancers through loop extrusion, enabling tight enhancer mediated control of gene regulation. Supporting this idea, mouse homologues of some of the genes whose E-P loops overlap with differential TADs (Supplementary Table 3d), including CNTN5, CNTNAP2, CNTNAP5, FLTR2, FLRT3, GABRA1, and GRIA4, have been shown to be downregulated in mouse cortical neurons upon knockdown of the cohesin component RAD21 42 . As we detect active enhancer enrichment downstream of neuronal TAD boundaries, this may imply a predominantly asymmetric loop extrusion mechanism that reels distal enhancers located downstream towards the promoter.…”
Section: Discussionmentioning
confidence: 89%
“…This, and similar observations made in a parallel study on the Shh locus 52 , argues that we may need to better define the meaning of 'long-range' when discussing mechanisms of gene activation. We postulate that the type (strength) of the enhancer and the genomic context determines whether the enhancer relies on cohesin-dependent or -independent mechanisms 25,28 to fully activate a target gene over intermediate distances (let's say 0-100kb). Molecular condensates formed through non-specific interactions between intrinsically disordered domains of enhancer-and promoter-associated transcription factors and Mediator may enable cohesin-independent E-P communication over such 12 distances [53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…This raised doubts about whether chromatin looping was really necessary for enhancers to control gene expression over distance, doubts that were further fueled by live cell microscopy studies that sometimes 21 but not always 22,23 found enhancers in closer proximity to the genes that they activated. Yet, other studies did observe that cohesin depletion caused loss of promoter-enhancer contacts 24,25 and reduced enhancer-dependent expression [24][25][26][27] of many, but not all genes, suggesting that both cohesin-dependent and -independent mechanisms exist for long-range gene regulation 25,28 . Acute depletion of WAPL, the factor that releases cohesin from chromatin, caused repositioning of cohesin from tissue-specific enhancers to CTCF boundaries, disrupted enhancer-promoter looping and down-regulated expression of tissue-specific genes controlled by such enhancers 24 .…”
Section: Introductionmentioning
confidence: 96%